2002
DOI: 10.1046/j.1365-2133.2002.04716.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors associated with hand dermatoses: which subgroup needs additional psychological care?

Abstract: Psychological factors should be taken into consideration in the treatment of patients with HD. High-SR patients with a negative patch-test seem to require more adjuvant psychological care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 22 publications
8
70
0
7
Order By: Relevance
“…For example, a close relationship between itch and psychological factors has been demonstrated in hand dermatoses, especially in patients who were convinced that stress was a major trigger of their disease (76).…”
Section: Psychoemotional Stress Triggers or Enhances Itchmentioning
confidence: 99%
“…For example, a close relationship between itch and psychological factors has been demonstrated in hand dermatoses, especially in patients who were convinced that stress was a major trigger of their disease (76).…”
Section: Psychoemotional Stress Triggers or Enhances Itchmentioning
confidence: 99%
“…A cumulative score is determined by adding the scores of the individual items. The responders were grouped on the basis of their Beck Depression Inventory total scores by means of the following classification: (1) no or minimal depression (score, 0-13), (2) mild depression (score, [14][15][16][17][18][19], (3) moderate depression (score, [20][21][22][23][24][25][26][27][28], and (4) severe depression (score, .…”
Section: Depression and Health-related Qolmentioning
confidence: 99%
“…10,[15][16][17] It has been suggested that patients with contact dermatitis may experiencedepressivesymptoms. [18][19][20] Sofar,nodata are available on the possible associations between depression and the prognosis of patients with OHE. Poor socioeconomic status has been shown to affect outcome adversely in many chronic disorders, but no current data are available for patients with OHE.…”
mentioning
confidence: 99%
“…De los estudios comunitarios realizados en Noruega 4,6 y otros países [7][8][9] , sabemos que los individuos con picazón en la piel, eccema y psoriasis tienen el doble de probabilidades de estar deprimidos que la población en general 10 . Se ha demostrado que la depresión comórbida, la ansiedad y la ideación suicida son comunes en pacientes con afecciones cutáneas 11 .…”
Section: Impacto Psicológico Del Cáncer De Piel En La Vejezunclassified